Karakteristik Fisik dan Uji Iritasi Krim Pelembab Maskne Kombinasi Minyak Biji Labu Kuning (Cucurbita moschata Seed Oil) Dan Niasinamide: Physical Characteristics and Irritation Test of Maskne Moisturizing Cream Combination of Pumpkin Seed Oil (Cucurbita moschata Seed Oil) and Niacinamide - Sunnah, Istianatus; Tiara Anggraeni; Fadiyah, Ghina Atika; Erwiyani, Agitya Resti (Journal of Holistics and Health Sciences, 2024)
Face masks that are used too long and often cause acne called maskne. The emergence of acne can be overcome by using a moisturizer. One of the ingredients that can be added to the moisturizer formula is niacinamide. This substance has potential anti-inflammatory activity to treat acne vulgaris. In the maskne formulation, vegetable oil can be added as an emollient, one of which is pumpkin seed oil. The purpose of this study was to analyze the content of pumpkin seed oil metabolite compounds and evaluate the physical characteristics of maskne moisturizing cream. The variation of pumpkin seed oil concentration used was 5% and 10%. Identification of the content of metabolite compounds in pumpkin seed oil was carried out qualitatively. Physical properties were observed for 4 weeks. Dermal irritation test refers to BPOM 2014. The physical characteristics of the preparation were analyzed by one way ANOVA. Organoleptic and homogeneity observations were analyzed descriptively. Phytochemical screening of pumpkin seed oil contains flavonoids and saponins. Organoleptic observations, the cream preparation was homogeneous, semi-solid, white in color, thick in shape and odorless. The cream has a pH of ± 8, adhesion for 1.13-1.60 seconds, spreading power in a diameter of 5.11-5.54 cm, and viscosity of 7376-10014.67 cP. No edema and erythema were found after application to the skin. Pumpkin seed oil contains flavonoids. MBLK maskne moisturizing cream combined with niacinamide meets the physical characteristics of pH, spreading power, adhesion, viscosity, centrifugation and non-irritating.   ABSTRAK Masker penutup wajah yang digunakan terlalu lama dan sering menyebabkan timbulnya jerawat yang disebut maskne. Timbulnya jerawat tersebut dapat diatasi dengan penggunaan pelembab. Salah satu bahan yang dapat ditambahkan dalam formula pelembab yaitu niasinamid. Zat ini memiliki aktivitas anti inflamasi yang potensial untuk mengobati akne vulgaris. Dalam formulasi maskne dapat ditambahkan minyak nabati sebagai emolient salah satunya minyak biji labu kuning. Tujuan penelitian ini untuk menganalisis kandungan senyawa metabolit minyak biji labu kuning dan mengevaluasi karakteristik fisik krim pelembab maskne. Variasi konsentrasi minyak biji labu kuning yang digunakan 5% dan 10%. Identifikasi kandungan senyawa metabolit dalam minyak biji labu kuning dilakukan secara kualitatif. Sifat fisik diamati selama 4 minggu. Uji iritasi dermal mengacu pada BPOM 2014. Karakteristik fisik sediaan dianalisis dengan one way ANOVA. Pengamatan organoleptis dan homogenitas dianalisis secara deskriptif. Skrining fitokimia minyak biji labu kuning mengandung flavonoid dan saponin. Pengamatan secara organoleptis, sediaan krim homogen, semi padat, berwarna putih, bentuk kental dan tidak berbau. Krim memiliki pH ± 8, daya pelekatan selama 1,13-1,60 detik, daya penyebaran dalam diameter 5,11-5,54 cm, dan viskositas 7376-10014,67 cP. Tidak ditemukan udema dan eritema setelah diaplikasikan di kulit. Minyak biji labu kuning mengandung flavonoid. Krim pelembab maskne MBLK kombinasi dengan niasinamid memenuhi karakteristik fisik pH, daya sebar, daya lekat, viskositas, sentrifugasi dan tidak iritatif.